2020
DOI: 10.4103/ijpvm.ijpvm_141_19
|View full text |Cite
|
Sign up to set email alerts
|

Reflex gastroesophageal disorders and functional dyspepsia: Potential confounding variables for the progression of chronic periodontitis: A clinical study

Abstract: Aim: To probe into the possible connection between gastroesophageal reflux disorders (GERDs) and functionally occurring dyspepsia as a factor raising the risk of chronic periodontitis. Materials and Methods: A cross-sectional study was carried out on 40 patients with chronic periodontitis with age group between 40–60 years. The test group included 20 people diagnosed with gastroesophageal reflux disease (GERD), according to the Montreal Definition and Classification agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In contrast to these results, Katle et al [23] found a lower pepsin concentration in patients than controls, and they explained this by GER inducing hypersalivation that may dilute the pepsin concentration in those patients [29] .…”
Section: Discussionmentioning
confidence: 84%
“…In contrast to these results, Katle et al [23] found a lower pepsin concentration in patients than controls, and they explained this by GER inducing hypersalivation that may dilute the pepsin concentration in those patients [29] .…”
Section: Discussionmentioning
confidence: 84%
“…Currently, there is no evidence that supports any associations of chronic periodontitis with GERD risk. Some available observational studies showed that the risk of chronic periodontitis was increased among GERD patients [14][15] . GERD was an independent risk factor for chronic periodontitis in these two studies with consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies found that chronic periodontitis is likely to be associated with GERD because poor salivary function or microbial colonization caused by GERD can contribute to poor oral health 5 . Individuals with GERD are at risk of chronic periodontitis [14][15] . Nevertheless, GERD is an independent risk factor or potential confounder of chronic periodontitis, and its consequences are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Data from studies on the etiology of periodontal disease suggest a strong association between periodontal disease and GERD. [ 11 , 12 ] The saliva is rich in mucins, which covers the adjacent teeth and periodontal tissue surfaces via infiltration, and forms a natural protective barrier against external microbiological, chemical, and mechanical damage. [ 13 ] However, in a trial of patients with and without GERD, no statistical differences have been reported in salivary flow rate, buffering capacity, oral clinical examination, or palatal mucosal histopathology.…”
Section: Introductionmentioning
confidence: 99%